2018
DOI: 10.3390/molecules23061433
|View full text |Cite
|
Sign up to set email alerts
|

Application of a JA-Ile Biosynthesis Inhibitor to Methyl Jasmonate-Treated Strawberry Fruit Induces Upregulation of Specific MBW Complex-Related Genes and Accumulation of Proanthocyanidins

Abstract: Fleshy fruits are an important source of anthocyanins and proanthocyanidins (PAs), which protect plants against stress, and their consumption provides beneficial effects for human health. In strawberry fruit, the application of exogenous methyl jasmonate (MeJA) upregulates anthocyanin accumulation, although the relationship between the jasmonate pathway and anthocyanin and PA biosynthesis in fruits remains to be understood. Anthocyanin and PA accumulation is mainly regulated at the transcriptional level throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 78 publications
3
41
0
Order By: Relevance
“…To understand to some extent, the physiological and molecular mechanism underlying the defense response of MeJA-treated fruit, we analyzed changes in lignin and anthocyanin contents and defense-related gene expression in the harvested treated fruit. According to literature, MeJA treatment not only upregulated defense-related gene expression but also promoted the secondary metabolism, particularly through the activation of the phenylpropanoid pathway [16,27,28]. In this sense, we observed that M3 treatment promoted both a higher level of anthocyanin and lignin accumulation with respect to control fruits at postharvest (0 hpi) ( Figure 2).…”
Section: Anthocyanin and Lignin Accumulation And Upregulation Of Jasmsupporting
confidence: 70%
See 2 more Smart Citations
“…To understand to some extent, the physiological and molecular mechanism underlying the defense response of MeJA-treated fruit, we analyzed changes in lignin and anthocyanin contents and defense-related gene expression in the harvested treated fruit. According to literature, MeJA treatment not only upregulated defense-related gene expression but also promoted the secondary metabolism, particularly through the activation of the phenylpropanoid pathway [16,27,28]. In this sense, we observed that M3 treatment promoted both a higher level of anthocyanin and lignin accumulation with respect to control fruits at postharvest (0 hpi) ( Figure 2).…”
Section: Anthocyanin and Lignin Accumulation And Upregulation Of Jasmsupporting
confidence: 70%
“…In the M1 treatment, the absence of correlation between the FaPOD27 and FaANR expression levels with the lignin and anthocyanin accumulation patterns at 0 hpi, respectively, may be due to the participation of other genes or gene family members belonging to the phenylpropanoid pathway that we did not analyze. It has been shown that MeJA treatment upregulates most of the phenylpropanoid pathway-related genes in F. chiloensis fruits [16], and the existence of several gene family members for anthocyanin biosynthesis has been evaluated in Fragaria species [27].…”
Section: Anthocyanin and Lignin Accumulation And Upregulation Of Jasmmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that proanthocyanidin (PA) accumulation in developing strawberry and grape berry showed a similar pattern to JA-Ile, occurring early in fruit development and decreasing as the fruit ripens [179,180]. We observed an increase in PA content by the application of a chemical inhibitor for the key JA-Ile biosynthetic enzyme JAR1, suggesting that the JA pathway could be related to PAs biosynthesis in strawberry fruit [181].…”
Section: Jasmonatesmentioning
confidence: 54%
“…The composition of the fruits, although representing a characteristic of each species, can be influenced by a number of factors (as presented in Table 2), including the characteristics of the cultivar [21,27,29,31,34,39,[43][44][45][46], cultivation factors, and the environmental conditions [18,27,37,38,[47][48][49][50], ripening stage [28,29,35,51], or by biotechnological approaches [52][53][54]. For example, the variation in composition of a large number of Fragaria × ananassa Duch.…”
Section: Anthocyaninsmentioning
confidence: 99%